Oral antibiotics relieve allergic asthma in post-weaning mice via reducing iNKT cells and function of ADRB2 - Li, Na; Chen, Jie; Xie, Sitao; Zhang, Meng; Shi, Tianyun; He, Yanchao; Jie, Zhijun; Su, Xiao (Frontiers in Immunology, 2022)
The role of normal gut microbiota in asthma or ovalbumin (OVA)-induced asthma tolerance (OT) remains unclear. Here, we established mouse models of asthma and OT followed by 2 weeks of antibiotic treatment, to clear the gut microbiota. Antibiotic treatment was found to alleviate allergic asthma accompanied with a reduction of invariant natural killer (iNKT) cells. By RNA-seq analysis, we found that β-adrenergic receptor (ADRB) genes, including Adrb1, Adrb2, and Adrb3, were downregulated in asthmatic lungs, but these changes were reversed in OT lungs. Moreover, Adrb2 and Adrb3 were significantly upregulated in asthmatic lungs after antibiotic treatment. Surprisingly, blocking ADRB with propranolol relieved allergic asthma while reducing T helper 2 (Th2) and Treg cell numbers. Further analyses using flow cytometry and immunofluorescence showed that the protein expression level of ADRB2 was higher in asthmatic lungs than that in the control and OT lungs. Notably, dendritic cells (DCs), especially the ADRB2+ DCs, were increased in asthmatic lungs compared to that in the control and OT lungs. In addition, ADRB2+ DCs were significantly reduced following the administration of the ADRB2-specific antagonist ICI118551. Our findings suggest that antibiotic treatment can alleviate OVA-induced allergic asthma via reducing the frequency of iNKT cells and function of ADRB2.